PENERIMAAN SISWA TERHADAP METODE BERMAIN PERAN UNTUK BERBICARA DIKELAS DWIBAHASA KELAS V SDIT AL-MUZZAMMIL - Fadhil, Muhammad Rizky (Akademika : Jurnal Teknologi Pendidikan, 2025)
This research focuses to examine students’ reception towards the use of the role-play method in the teaching and learning process to improve their English-speaking skills. The method used in this research is a qualitative approach, with classroom observation as the main technique for collecting data, along with directly asking fifth-grade elementary school students about their experiences using role-play in English learning activities. Based on the analysis of the observations and the students’ answers, the majority of them greatly enjoyed the role-play method, and judging from their increased activeness in speaking, the method successfully created an engaging and active learning atmosphere.